2018
DOI: 10.15761/tim.1000152
|View full text |Cite
|
Sign up to set email alerts
|

Nitrotyrosine as a biomarker: recovery of histopathological atherogenic lesions in rats treated with ascorbic acid

Abstract: Aims: To value the antioxidant effect of vitamin C on atherogenesis induced by oxidative stress, using nitric oxide, superoxide dismutase and nitrotyrosine as biomarkers.Main methods: Wistar rats were used: (A) Control; (B) Proinflammatory Induction for 30 days, (C) Proinflammatory Induction for 30 days+Vitamin C, (D) Proinflammatory Induction for 60 days and (E) Proinflammatory Induction for 60 days+Vitamin C. Proinflammatory Induction with adrenaline (0.1 mg/day/rat). Vitamin C (2,14 mg/day/rat) administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The formation of nitrotyrosine represents a specific peroxynitrite-mediated protein modification and is considered as a biomarker for endogenous peroxynitrite activity. Our results correlated with the results of Baez et al (2018). It is tempting to speculate that the contributing factor to enhanced oxidative stress after co-application was the decreased activity of SOD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The formation of nitrotyrosine represents a specific peroxynitrite-mediated protein modification and is considered as a biomarker for endogenous peroxynitrite activity. Our results correlated with the results of Baez et al (2018). It is tempting to speculate that the contributing factor to enhanced oxidative stress after co-application was the decreased activity of SOD.…”
Section: Discussionsupporting
confidence: 89%
“…Schreckenberg et al (2015) found that the RV is exposed to higher oxidative stress damage as detected by dihydroethidium staining for superoxide and measurements of peroxynitrite. The quantification of nitrotyrosine indirectly demonstrates the production of peroxynitrite and oxidative damage in endothelial cells (Baez et al 2018). There were differential superoxide levels between the two ventricles that may be caused by varied expression of manganese SOD.…”
Section: Discussionmentioning
confidence: 99%
“…It can react with amino acids like tyrosine, leading to the formation of nitrotyrosine, dityrosine, and protein oligomers [ [6] , [7] , [8] ]. Nitrotyrosine and dityrosine are known as markers of inflammation and oxidative stress, which can influence the chemical and physiological properties of proteins [ [9] , [10] , [11] ]. For example, nitration can change the binding of proteins to certain receptors and thus modulate downstream signaling cascades [ 7 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These modifications affect protein structure and function and are associated with various diseases (1)(2)(3). They serve as biomarkers of oxidative damage in proteins, providing insight into the role of oxidative stress in disease development and progression (4)(5)(6). These tyrosine modifications also play a crucial role in altering the immune responses to allergens and may contribute to the increasing prevalence of allergic diseases and their association with traffic-related air pollution (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%